The Influence of the "Log in" Podcast as a Da'wah Media in Strengthening Religious Tolerance among UINSU Students: The Influence of the "Log in" Podcast as a Da'wah Media among UINSU Students - Pohan, Sarhul Azkar; Bahrin, Andini Nur (AL-IDZAAH: Jurnal Dakwah dan Komunikasi, 2025)
This study investigates the impact of the "Login" Podcast on enhancing religious tolerance among UINSU students. Hosted on Deddy Corbuzier’s YouTube channel by Habib Ja'far Husein and Onadio Leonardo, the podcast discusses diversity and tolerance in a casual yet substantive manner. Using a quantitative approach with Simple Random Sampling of 100 students, the results indicate that students frequently use YouTube for entertainment and learning, with the "Login" Podcast being a favored content. The regression analysis shows a significant positive correlation between viewing frequency and increased understanding and reinforcement of tolerance, evidenced by a t-value of 10.970 (above the t-table of 1.664) and a coefficient of determination of 55.6%. This suggests that the podcast significantly influences the strengthening of tolerance values among UINSU students.